2016
DOI: 10.1088/1741-2560/13/3/036006
|View full text |Cite
|
Sign up to set email alerts
|

Gait adaptation to visual kinematic perturbations using a real-time closed-loop brain–computer interface to a virtual reality avatar

Abstract: Objective The control of human bipedal locomotion is of great interest to the field of lower-body brain computer interfaces (BCIs) for gait rehabilitation. While the feasibility of closed-loop BCI systems for the control of a lower body exoskeleton has been recently shown, multi-day closed-loop neural decoding of human gait in a BCI virtual reality (BCI-VR) environment has yet to be demonstrated. BCI-VR systems provide valuable alternatives for movement rehabilitation when wearable robots are not desirable due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 49 publications
2
67
0
Order By: Relevance
“…Pearson's correlation coefficient (r-value) was used in our previous studies to measure performance 18,25 .…”
Section: Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pearson's correlation coefficient (r-value) was used in our previous studies to measure performance 18,25 .…”
Section: Metricsmentioning
confidence: 99%
“…Experiment 1: Decoding based on delta band features. The protocol for Experiment 1 is equivalent to the real-time decoding pipeline used in the previous studies 18,25 . This is the baseline data processing pipeline, which will be used as a comparison for the following two experiments.…”
Section: Metricsmentioning
confidence: 99%
“…Previous studies have shown that low delta band (0.1–2 Hz) EEG contains intended movement-related information for decoding the kinematics of lower limb or gait states (Presacco et al, 2011, 2012; Jorquera et al, 2013; Kilicarslan et al, 2013; Bulea et al, 2014; Luu et al, 2016). For example, in Presacco et al (2011), Presacco et al (2012), and Luu et al (2016), it was shown that delta band EEG contains information about gait movement kinematics that can be decoded using Wiener or Kalman filters. In Kilicarslan et al (2013), Jorquera et al (2013), and Bulea et al (2014), it was shown that movement-type (e.g., “stop,” “go,” etc.)…”
Section: Introductionmentioning
confidence: 99%
“…An adaptive approach was taken in (Hsu S. H. et al, 2016), who developed a optimized online recursive ICA algorithm (ORICA) using online recursive least squares (RLS) for real-time blind source separation (BSS), which is of obvious interest and use to BCI. Another interesting study was (Luu T. P. et al, 2016), who used closed-loop EEG-based BCI system for controlling the gait of a virtual avatar in VR in a BCI-VR setting. They used slow cortical potentials (0.1-3Hz) activity, achieving R values of around 0.4 for joint control of the virtual avatar on average.…”
Section: Introductionmentioning
confidence: 99%